Balance aparente de nutrientes en la zona norte-central de Nicaragua (Matagalpa-Jinotega) - Bejarano Silva, Wilfredo José; Maldonado Rivera, Juan Ramón; Eresue, Michel. Asesor; Salmerón Miranda, Francisco. Asesor (Managua (Nicaragua), 1999)
Sumario (Es)
Ilus.; 24 ref.
Tesis (Ing Agr)
Keywords: ZEA MAYS; PHASEOLUS VULGARIS; ORYZA SATIVA; NUTRIENTES; FERTILIDAD DEL SUELO; ABONOS VERDES; ROTACION DE CULTIVOS; SUELO; ZONIFICACION DE SUELOS; COMPOSICION QUIMICA; BIOMASA; TAMAÑO DE LA FINCA; NICARAGUA; SUELO Y FERTILIZANTES; BALANCE DE NUTRIENTES; MATAGALPA; JINOTEGA; REGION VI